Design an electronically-amplified stethoscope (for listening to your heart and lung sounds) - Tan, Miko Hui Min (Nanyang Technological University, 2022)
With the global rise in heart disease, detecting any critical signals that might lead to severe complications if left untreated is crucial. Each year there are an estimated 17.8 million deaths relating to cardiovascular diseases [1] The use of a stethoscope helps to detect this abnormality of cardiovascular disease. The most common stethoscopes used currently in the medical fields are acoustic stethoscopes. However, with the rise of technological advancement, an electronic stethoscope might be adopted in the near future as a point of care instrument for detecting cardiac arrhythmia. An electronic stethoscope has the ability to amplify low-level sounds and signal recording, which an acoustic stethoscope lags. In this project, students will appreciate and understand the fundamental functions of an electronic stethoscope by designing an electronically amplified stethoscope with theoretical knowledge of analog electronics taught in class. The design will be divided into three stages, operational amplifier, volume unit, and power meter. Ultimately, students are capable of analyzing and hearing their heart pulses through this experimental project.